Associations Between Parental Monitoring and Multiple Types of Youth Violence Victimization: A Brief Report. Issue 19 (October 2022) - Khetarpal, Susheel K.; Szoko, Nicholas; Culyba, Alison J.; Shaw, Daniel; Ragavan, Maya I.
Youth violence victimization continues to be pervasive and a significant cause of adolescent mortality. Since their 2014 "Connecting the Dots" report, the Centers for Disease Control and Prevention have encouraged researchers to identify shared protective factors that prevent multiple forms of youth violence. Parental monitoring, a bidirectional construct encompassing parental knowledge and regulation of their child's activities with children's concurrent perception of their parent's awareness of such activities, could be such a cross-cutting protective factor. In this study, we examined associations between parental monitoring and multiple types of violence victimization among a school-based sample of adolescents. We conducted a cross-sectional analysis of an anonymous survey of health risk and protective behaviors completed by students across Pittsburgh Public Schools ( N = 2, 426). In separate analyses, we used logistic regression to examine associations between youth-reported parental monitoring and multiple experiences of youth violence victimization, ranging from school- and electronic-based bullying to different forms of sexual and physical violence. We found that many experiences of youth violence victimization were consistent with nationally representative data. In addition, we determined that higher parental monitoring was significantly and inversely associated with all violence victimization outcomes examined (school-based bullying, electronic-based bullying, threatening someone with a weapon, adolescent relationship abuse, sexual assault, and exchange sex) at the p < .05 threshold. Overall, this study is one of the first that examines how parental monitoring relates to multiple forms of youth violence victimization, including exchange sex, which is a critical but less-studied violence experience. This work adds to the growing literature on how parental monitoring may serve as a shared protective factor for multiple forms of violence victimization.